Fourth industrialization-oriented offsite construction: case study of an application to an irregular commercial building. Issue 9 (9th May 2020) - Moon, Sungkon; Ham, Namhyuk; Kim, Sungjin; Hou, Lei; Kim, Ju-Hyung; Kim, Jae-Jun
Abstract : Purpose: This study, a research project, aims to examine the distinct characteristics of the Fourth Industrial Revolution (4IR), with a focus on construction. Following this examination, the paper presents a field study to evaluate the impact of the 4IR on the construction process. Design/methodology/approach: The first half of this project is dedicated to defining the 4IR by reviewing existing literature. The other half of the project presents a case study to demonstrate the concept of the 4IR and measure the effect of its application. To validate the defined concept of the 4IR, the study focuses on the following: autonomous system for producing drawings and robotics in construction. Findings: The intensive literature review revealed three unequivocal features of the 4IR: defined tasks, undefined tasks and improvement possibilities. The following case study showed that the incorporation of the three 4IR features resulted in improved productivity and efficiency during the construction of the podium for the Lotte World Tower. For example, the macro-based autonomous system achieved 5.52 shop drawings per hour, highlighting the potential impact of independent, autonomous machinery. Originality/value: The originality of this project stems from its attempt to quantify the effectiveness of applying autonomous technologies to a practical project. While previous works in this field have focused on system development and improvement, this paper presents an autonomous system at work in an actual project, in which junior engineers were able to be entirely replaced. The system was successful in independently creating numerous required shop drawings. The value of this analysis is to generate scientific evidence to evaluate the efficacy of the adoption of 4IR-oriented technologies.